Copyright Protection for Applied Art and Works of Artistic Craftsmanship After Star Athletica - Ginsburg, Jane C. (The Columbia Journal of Law & the Arts, 2020)
As the very first session proclaimed, the Star Athletica case has not been a model of total clarity on the Supreme Court’s part. I’m going to explore that proposition. I will go through some basic elements of the copyright statute, and will then apply those rules to several examples. The Copyright Act sets out the category of pictorial, graphic, and sculptural (“PGS”) works, whose statutory definition includes applied art. That was the subject matter at issue in Star Athletica. The statute also provides that PGS works “shall include works of artistic craftsmanship insofar as their form but not their mechanical or utilitarian aspects are concerned.” “Works of artistic craftsmanship” has been a somewhat overlooked category, but I think, as a result of Star Athletica and also the pending amendments of the Compendium of U.S. Copyright Office Practices, that this category will receive a lot more attention. It does not, however, necessarily follow that the meaning of that category will be any clearer than the standard for what is a PGS work.